DEVELOPING INSTAGRAM APPLICATION-BASED MEDIA TO OPTIMIZE STUDENT LEARNING OUTCOMES OF THE NATURAL SCIENCE EDUCATION DEPARTMENT UNIMA - Yohanes Bery Mokalu; Ester Caroline Wowor; Widya Anjelia Tumewu (LPPM Politeknik Saint Paul Sorong, 2022)
This study aims to develop an Instagram application-based learning media in the Department of Science Education, State University of Manado. The research started from March 2022 to June 2022, using the Research and Development (R&D) method by Borg & Gall modified with Prof Suparman's MPI model. The results of the study were in the form of science learning media products based on Instagram applications consisting of Instagram accounts, animations, videos, and learning materials. The results of the evaluation media experts with a score of 4.4, material expert validation with a value of 4.6, one-on-one test with a value of 3.2, and small group test with a value of 3.4, after being analyzed as a whole, the value of the product is in the 'very good' category. and worth to use'